Synthesis of carbon dots as an antibacterial and antioxidant agent - Zhang, Ying; Wang, Jie; Wu, Xiuhong; Chang, Rui; Luo, Hongyu; Yang, Juan; Wu, Quan; Xu, Ze; Zhong, Yingfu (Frontiers in Chemistry, 2025)
ObjectiveA new type of antibacterial and antioxidant carbon dots has been discovered.MethodsIn this study, a facile one-step hydrothermal method was employed to synthesize carbon dots (CDs) using Yongchuan Xiuya as the precursor.ResultsThe morphology and chemical composition of the synthesized CDs were systematically characterized. The resulting doped carbon quantum dots (CDs) exhibited a spherical shape with an average particle size of 4.17 nm and a lattice spacing of 0.22 nm. The CDs demonstrated exceptional antioxidant and antibacterial properties, showing significant antimicrobial activity against both Gram-positive (S. aureus) and Gram-negative (E. coli) bacteria, with minimum inhibitory concentration values of 0.62 mg/mL and 0.85 mg/mL, respectively. Mechanistic studies revealed that bacterial cell death likely results from strong electrostatic interactions between the negatively charged bacterial surfaces and the positively charged CDs.ConclusionThis work presents a cost-effective and eco-friendly approach to producing carbon dots with dual functionality as both antibacterial and antioxidant agents.